Financial Soundness Indicators Compilation Guide 2019. - International Monetary Fund. Statistics Dept. (Washington, D.C. : International Monetary Fund, 2019)
The 2019 Financial Soundness Indicators Compilation Guide (2019 Guide) includes new indicators to expand the coverage of the financial sector, including other financial intermediaries, money market funds, insurance corporations, pension funds, nonfinancial corporations, and households. In all, the 2019 Guide recommends the compilation of 50 FSIs-13 of them new. Additions such as new capital, liquidity and asset quality metrics, and concentration and distribution measures will serve to enhance the forward-looking aspect of FSIs and contribute to increase policy focus on stability of the financial system.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet